IMPLEMENTASI MANAJEMEN TALENTA KARYAWAN DI BELIKOPI - Ningsih, Yuliya Trisna; Subagyo, Subagyo; Widodo, Moch. Wahyu (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims to determine the implementation of talent management, employee recruitment and development in Belikopi. The research approach used is qualitative, and is a type of case study research. The informants in this study were 3 Belikopi employees aged 20 to 40 years. The data were collected by observation, documentation and interview methods. Furthermore, the data were analyzed using data triagulation techniques. The results of the study show that the implementation of talent management, recruitment and development in Belikopi has not been maximized because there is no roadmap of written rules regarding talent management and its implementation